The Wild Robot - Nyong'o, Lupita; Pascal, Pedro; O'Hara, Catherine; Nighy, Bill; Connor, Kit; Hsu, Stephanie; Hamill, Mark; Berry, Matt; Rhames, Ving ([United States] : Dreamworks Animated, 2024)
The epic adventure follows the journey of a robot, Rozzum unit 7134, 'Roz' for short, that is shipwrecked on an uninhabited island and must learn to adapt to the harsh surroundings, gradually building relationships with the animals on the island and becoming the adoptive parent of an orphaned gosling.
12/03/2024
new dvd 2024 winter.
Director, Christopher Sanders.
Lupita Nyong'O, Pedro Pascal, Catherine O'Hara, Bill Nighy, Kit Connor, Stephanie Hsu, Mark Hamill, Matt Berry, Ving Rhames.
MPAA rating: PG.
DVD.
Keywords: Children's films; Action/Adventure.; Science Fiction; Animated; Children's.